Usage of robotic rehabilitation technology for lower limbs therapy of children with cerebral palsy - A review - Mahamud F.; Anuar A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Diseases; Manufacture; Patient rehabilitation; Cerebral palsy; Children with cerebral palsies; Lower limb; Robotic rehabilitation; Robotic technologies; therapy; Robotics